Evaluating Pharmaceutical Care Services in Promoting Public Health Outcomes within the Community - Lusine Nazaryan; Anush Barseghyan; Marta Simonyan (Indian Journal of Public Health)
In developing countries, consumer awareness about self-medication risks is low. Pharmacists, acting as primary health-care providers, are pivotal in offering pharmaceutical care in these communities. The primary objective of this research was to assess pharmaceutical care provided by pharmacy employees and analyze consumer satisfaction. The survey, conducted from 2021 to 2022 through an anonymous questionnaire, involved 1308 respondents. The study revealed a significant preference for self-medication (56.7%) without seeking professional guidance, attributed to inadequate advice from pharmacy staff, leading to reduced confidence in their recommendations. Improving the professional behavior of the Armenian pharmacy employees through investment in training and guidelines is crucial for their integration into primary health care.